THE VULNERABILITY OF MONGOLIAN ECONOMY TO CLIMATE CHANGES - Erdenekhuu, Khaliunaa (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Nowadays climate change is one of the greatest global problems that affects in different extent particular countries and regions. Negative impact of global warming shows not only in form of ecosystem degradation, but also in affecting societies and economies. In this paper, based on available literature, a vulnerability of economy and society of Mongolia to climate change was presented. It is a starting point for assessment of adaptive capabilities of socio-economic system of Mongolia.